Can changes in sentiments influence consumer behavior? Evidence from the Trump‐Russia investigation. (14th July 2021) - Biolsi, Christopher; Lebedinsky, Alex
Abstract: We examine the hypothesis that animal spirits might affect economic behavior by analyzing how consumer spending changes in response to the news coverage of the investigation into coordination between Donald Trump's presidential campaign and Russia. Using daily consumption data, we find that Republicans and Democrats responded differently to the news. Increased media coverage led households in counties that voted for Hillary Clinton to spend less: On the days of heaviest news coverage, spending declined by 0.007 to 0.011 per household member for every point added to Clinton's vote share. There is evidence that in Republican counties, the coverage had opposite effects.